Bishop Andrey (Ukhtomsky): Church Comprehension and Criticism of Ideology and Practice of Socialism - A. A. Ivanov (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The question of the attitude of the famous church publicist Bishop Andrey (Ukhtomsky) to the theory and practice of socialism in Russia and the USSR is considered. For the first time, the views of the bishop on the similarities and differences between socialist ideology and the Orthodox faith, starting with the events of the First Russian Revolution and ending with the Soviet period, are reconstructed and analyzed. Particular attention is paid to Andrey (Ukhtomsky)’s criticism of socialism, professed by left political forces and attempts to oppose it with a different socialism, which the church publicist called Christian and ecclesiastical. The legitimacy of classifying the bishop as a supporter of Christian socialism is questioned and a view is proposed according to which Bishop Andrey’s opposition to political socialism was forced and was intended to deprive the socialists of the monopoly on knowledge about the just reorganization of society, as well as to conduct polemics with the adherents of socialism in a way they understand language. It is argued that changing political views and attitudes towards various forms of state power throughout his life, Andrey (Ukhtomsky) remained consistent in upholding his views, both on the nature of socialism and on the ways to overcome it.